Tell no lies [large type] - Hurwitz, Gregg Andrew (Thorndike Press, 2013)
Disappointing his old-money San Francisco mother, Daniel Brasher left a career as a money manager to marry a community organizer and work at a job he loves, doing group counseling with recent parolees. About to move into private practice, Daniel finds a note in his mailbox: Admit what you've done or you will bleed for it. The deadline given had passed; the person it was meant for was brutally murdered. And this was only the beginning.